1998
DOI: 10.1177/000456329803500116
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Assays for Urinary Retinol-Binding Protein and β-2-Glycoprotein-1 Based on Commercially Available Standards

Abstract: Measurements of urinary retinol-binding protein (RBP) and beta-2-glycoprotein-1 (beta 2G1) provide sensitive indicators of proximal renal tubular malfunction. beta 2G1 is very stable in urine but RBP, which is much less stable, has been more extensively studied. We have designed two similar immunoassays allowing measurement of both proteins from one urine dilution. The assays both use widely available commercial standards and permit accurate measurement throughout most of the reference range. We measured both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…f Given by (excretion/4 h)/(volume of glomerular filtrate in 24 h); (volume of glomerular filtrate in 24 h) = 165.6 L (being 115 mL min −1 × 60 × 24/1000) (Denic et al 2019). g Sources for normal excretion were: β 2 -m (Bernard et al 1981); for RBP4, the dataset for healthy controls previously reported by Burling et al (2012) gave a mean of 0.80 ± 0.12 μg mmol −1 creatinine (± SEM); α 1 -m (Yu et al 1983); α1AG (Christiansen et al 2004); ZAG, see Methods; β2GI (Lapsley et al 1998);DBP (Lauridsen et al 2005); TTR (Beetham et al 1993); Alb (Silver et al 1986); Trf (Bernard et al 1990); IgG (Gohda et al 2012). h Given by [normal excretion in (nmol/mmol)/1000]/(Dent1 Excretion in μmol/mmol/0.90) × 100, assuming that protein excretion in Dent1 disease represents 90% of glomerular filtration.…”
Section: Ethical Approvalmentioning
confidence: 83%
“…f Given by (excretion/4 h)/(volume of glomerular filtrate in 24 h); (volume of glomerular filtrate in 24 h) = 165.6 L (being 115 mL min −1 × 60 × 24/1000) (Denic et al 2019). g Sources for normal excretion were: β 2 -m (Bernard et al 1981); for RBP4, the dataset for healthy controls previously reported by Burling et al (2012) gave a mean of 0.80 ± 0.12 μg mmol −1 creatinine (± SEM); α 1 -m (Yu et al 1983); α1AG (Christiansen et al 2004); ZAG, see Methods; β2GI (Lapsley et al 1998);DBP (Lauridsen et al 2005); TTR (Beetham et al 1993); Alb (Silver et al 1986); Trf (Bernard et al 1990); IgG (Gohda et al 2012). h Given by [normal excretion in (nmol/mmol)/1000]/(Dent1 Excretion in μmol/mmol/0.90) × 100, assuming that protein excretion in Dent1 disease represents 90% of glomerular filtration.…”
Section: Ethical Approvalmentioning
confidence: 83%
“…The baseline urinary excretion of markers for glomerular sizeselectivity (IgG) and for proximal tubular function (retinolbinding protein) were pathologically elevated in the 2 groups compared with normal controls (13Ϯ5 mg/d for IgG; 62Ϯ21 g/mmol creatinine for retinol-binding protein); values were similar to those of healthy subjects in previous studies. 19 The proximal marker retinol-binding protein was significantly reduced during pravastatin treatment compared with baseline, whereas IgG levels remained stable throughout the study.…”
Section: Effect On Renal Glomerular and Tubular Markersmentioning
confidence: 87%
“…Retinol-binding protein (RBP) was assayed as previously described using a polyclonal in-house sandwich ELISA [15]. Urinary N-acetyl-beta-D-glucosaminidase (NAG) activity was measured using a kit from PPR Diagnostics (London, UK).…”
Section: Methodsmentioning
confidence: 99%